Optimizing Data Embedding Through Coati-inspired Discrete Fourier Transform Techniques - S. S., Neetha; J., Bhuvana (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Information may be stored and retrieved efficiently because to cloud data embedding. Cloud platforms offer adaptable and scalable storage options, making it simple for customers to store and retrieve massive amounts of data as needed. Because of its scalability, businesses may adjust to their evolving data needs without being constrained by physical storage limits. It is mutual practice to manually alter the key limits used by data embedding approaches in an experimental form according to the application scenario and the picture. However, this can be a hassle and not work well in real-world situations. One optimisation technique that has recently been employed to increase performance is robust watermarking, which allows the critical operation parameter to be autonomously adjusted. Improved resilient watermarking approach in discrete Fourier transform via feast spectrum is projected in this research using the Coati optimisation algorithm (COA) in combination with visual info integrity and bit correct rate requirements. In particular, it optimises the watermark strength factor, number of bands, and frequency coefficients.